Regenerative medicine : a promising approach in overcoming diabetes as an increasing economic health burden / Nafeeza Mohd Ismail and Renu Agarwal - Nafeeza Mohd Ismail; Renu Agarwal (Faculty of Business and Management, 2015)
Diabetes mellitus is a serious public health issue, particularly in developing nations due to the cost associated with its management and its debilitating complications. Patients with diabetes mellitus type 1 are insulin-dependent due to complete loss of insulin producing beta cells in the pancreas and require a well-balanced regimen of insulin injections for life-time. The patients with diabetes mellitus type 2 also require insulin therapy in later stages of disease. In these patients insulin helps by correcting the insulin deficiency, however, the root cause of the disease still persists. Regenerative therapy is now offering solutions and hope to people with insulin-dependent diabetes. This paper gives an outline of the currently used methods in regenerative medicine that aim to re-establish the functional beta cells and restore the body’s original ability to regulate blood glucose levels.